2012
DOI: 10.1161/strokeaha.111.643098
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Improvement in Stroke-Prone Spontaneous Hypertensive Rats Related to the Pleiotropic Effect of Cilostazol

Abstract: Background and Purpose-Cerebral infarction is a major cause of death or decreasing activities of daily living. This study aimed to investigate the efficacy of commonly used antiplatelet drugs on stroke and motor and cognitive functions in relation to oxidative stress markers and insulin-like growth factor 1 receptor (IGF-1R). Methods-Stroke-prone spontaneously hypertensive rats were treated with vehicle, aspirin, clopidogrel, and cilostazol from 8 to 10 weeks of age. Physiological parameters, regional cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…In good agreement with our recent basic study in which cilostazol increased memory‐related insulin‐like growth factor‐1 receptor‐positive cells in the hippocampal CA1 region in stroke‐prone spontaneously hypertensive rats, cilostazol is especially effective on memory retention in patients with AD with asymptomatic lacunar infarction (Fig. ) …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In good agreement with our recent basic study in which cilostazol increased memory‐related insulin‐like growth factor‐1 receptor‐positive cells in the hippocampal CA1 region in stroke‐prone spontaneously hypertensive rats, cilostazol is especially effective on memory retention in patients with AD with asymptomatic lacunar infarction (Fig. ) …”
Section: Discussionsupporting
confidence: 91%
“…Cilostazol is an antiplatelet agent for preventing CVD, a potent type III phosphodiesterase inhibitor with neuroprotective effects, and improves cognition and regional cerebral flow in patients with AD with CVD and mild cognitive impairment . In addition, we have recently shown that cilostazol protected brains in stroke‐prone spontaneously hypertensive rats …”
Section: Introductionmentioning
confidence: 99%
“…Cilostazol was also assessed in chronic lacunar stroke for effects on forearm vascular reactivity , and acute lenticulostriate stroke for neurological deterioration . Experimentally, cilostazol may enhance white matter regeneration after ischemia (Supplement http://onlinelibrary.wiley.com/doi/10.1111/ijs.12466/suppinfo) ; in SHRSP, it both improved motor and cognitive function and reduced infarct size as compared with aspirin . Further trials of cilostazol beyond those listed in Supplementary http://onlinelibrary.wiley.com/doi/10.1111/ijs.12466/suppinfo are thought to be ongoing.…”
Section: Prostacyclin/cyclic Amp Systemmentioning
confidence: 99%
“…About 87% of patients with stroke are caused by ischemia, and ischemic stroke is induced by a loss of blood supply to part of the brain [3]. Prevention of ischemic stroke is thus of considerable importance [4,5,6,7], and it should be solved by some antiplatelet drugs, such as aspirin, which are commonly used in daily clinical settings for preventing stroke, recently [8]. …”
Section: Introductionmentioning
confidence: 99%